Androgen‐induced lncRNA POTEF‐AS1 regulates apoptosis‐related pathway to facilitate cell survival in prostate cancer cells. Issue 3 (3rd April 2017) - Misawa, Aya; Takayama, Ken‐ichi; Fujimura, Tetsuya; Homma, Yukio; Suzuki, Yutaka; Inoue, Satoshi
Abstract : Although long non‐coding RNAs (lncRNAs) have been associated with a variety of cancers, the interplay between lncRNAs and androgen receptor signaling in prostate cancer is still unclear. We identified an androgen‐dependent lncRNA, POTEF‐AS1, whose expression was regulated by androgen receptor in two androgen‐dependent cells by using directional RNA sequencing analysis. POTEF‐AS1 promoted cell growth, repressed genes related to the Toll‐like receptor signaling and apoptosis pathways, and inhibited apoptosis in docetaxel‐treated LNCaP cells. These findings suggest that POTEF‐AS1 would play a key role in the progression of prostate cancer by repressing Toll‐like receptor signaling. Abstract : We identified novel androgen‐regulated antisense lncRNA, POTEF‐AS1. It would play a key role in prostate cancer by repressing TLR signaling.